Tata Kelola Layanan Korban Kekerasan Rumah Tangga Berbasis Gender: Kasus KDRT di Jakarta Utara 2025 (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Gender-based domestic violence (KDRT) remains a critical issue in Indonesia, particularly in urban areas like North Jakarta. This study examines the governance of services for KDRT victims from a gender perspective in 2025, employing a qualitative case study approach. Data were gathered through in-depth interviews with 20 victims and service providers at community health centers (Puskesmas), the Women's Empowerment and Child Protection Agency (DP3A), and NGOs. Findings reveal fragmented governance, characterized by weak inter-agency coordination, low accessibility for low-income victims, and insufficient integration of gender perspectives in handling procedures. Key barriers include bureaucratic hurdles and inadequate training for staff on toxic masculinity issues. The study recommends an integrated governance model based on gender-responsive governance, including a one-stop digital platform and enhanced multi-stakeholder collaboration. Policy implications support the achievement of SDGs 5 and 16 at the local level. This study also highlights the importance of increasing public awareness and education regarding gender-based domestic violence to create a safer and more inclusive environment for victims.